POLA PENDAMPINGAN TEKNOLOGI PADA PROGRAM SWASEMBADA DAGING SAPI DAN KERBAU DI KABUPATEN REJANG LEBONG - Zul Efendi; Erpan Ramon (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2021)
AbstractÂ In order to meet production targets local beef at 420.3 thousand tons, the Ministry of Agriculture launched the Self-Sufficiency Program Beef (PSDS) in 2014, which consists of five principal program are: the provision of feeder / local beef, increased productivity and the reproducibility of local cattle, cuts prevention productive cows, cows provision, and setting domestic beef stock. In a way the problems encountered in the implementation of the Self-Sufficiency Acceleration Beef and Buffalo namely coordination and technical issues that are often caused by the slow process of technology transfer from the source to the users of technology. The purpose of this study was to determine the response of users to program and produce recommendations for improvement PSDSK implementation of assistance activities at the local level and Farmers. The experiment was conducted in Rejang Lebong for 8 months, starting in January to October 2011. Assessment is done by